Kepemimpinan Kepala Madrasah dalam Lembaga Pendidikan Islam - Wildan Nuril Ahmad Fauzi; Ahmad Noviansah; Mizaniya Mizaniya; Seka Andrean; Muhammad Sufyan Ats-Tsauri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The quality of a madrasa leader is the key to the success of education in this educational institution. leadership style encompasses how a person acts in an organizational context Good leadership is always associated with school success. There is a significant correlation between school performance and the effectiveness of a leader. This study aims to determine Islamic leadership in terms of theological perspective. The research method in this article is library research research using qualitative-interpretative data presentation. The research results of this journal are the Teacher as a leader in Islamic education with various terms that have moral, professional, and spiritual implications.